Shadow Banking and Systemic Risk in Europe and China - Sara Hsu; Jianjun Li; Yanzhi Qin (City, University of London, City Political Economy Research Centre (CITYPERC), 2013)
We compare the European and Chinese shadow banking systems. While the European shadow banking system is better developed than the Chinese shadow banking system, herd behavior and other factors in European markets create systemic risk, which contributed in part to the financial crisis. Dispersion of risk across the "under-developed" shadow banking system in China has led to some cases of localized, concentrated risk, but not to systemic risk. We discuss proposed European shadow banking regulation and its implications for systemic risk, and discuss what lessons China might glean from such policies. We also discuss what lessons China's diverse and systemically uncoordinated shadow banking sector might provide for Europe.
Keywords: 330